Hubungan Kualitas Tidur dengan Kadar Gula Darah pada Usia Remaja 15-17 Tahun - Tema Fo'arota Zendrato; Afnijar Wahyu (Poltekkes Kemenkes Padang, 2025)
Poor sleep quality can have a negative impact on health, including affecting blood sugar levels, especially in adolescents. Adolescence is a crucial period in physical and psychological development, so sleep quality disorders can trigger significant metabolic problems. The purpose of this study was to determine the relationship between sleep quality and blood sugar levels in adolescents aged 15-17 years at SMK Negeri 1 Percut Sei Tuan. This type of research is quantitative with a descriptive correlation design using a cross-sectional approach. The research sample involved 96 students who were selected using Simple Random Sampling. Data were collected through the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality and blood sugar levels using the glucometer method. Statistical tests used Spearman's rho. The results showed that the majority of respondents had poor sleep quality 63 respondents (65.6%) and blood sugar levels in the pre-diabetes category 48 respondents (50%). Statistical analysis showed a significant relationship between sleep quality and blood sugar levels (p-value = 0.000 or p<0.005), with a correlation coefficient (r) of 0.559. In conclusion, there is a significant and strong and positive relationship between sleep quality and blood sugar levels in adolescents aged 15-17 years.